2011
DOI: 10.1016/j.soilbio.2011.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Does moder development along a pure beech (Fagus sylvatica L.) chronosequence result from changes in litter production or in decomposition rates?

Abstract: International audienceThe development of temperate deciduous and conifers forests stands usually results in accumulation of forest floor organic matter and a shift from mull to moder humus forms. It has been suggested that an increase in nutrient uptake by trees during their rapid growth phase leads to topsoil acidification, decrease in earthworm density and thereby a decrease in litter turnover. The focus of this paper was to examine if the mull-moder shift with forest ageing results from higher leaf litter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…As a result of the decrease in the exploitation of non-timber forest products such as litter raking, and also due to the ageing of tree stands, a thicker layer of beech litter accumulates, which results in top soil acidification and lower concentrations of nutrients (Barbier et al, 2008;Trap et al, 2013). A shift from mull to moder humus form has previously been observed along the beech stand chronosequence (Trap et al, 2011). The properties of the topsoil such as moisture and nutrient loading could also be deteriorated by the fine root network of the ageing beech trees, which by the uptake of resources reduces soil water supply and nutrient availability (Barbier et al, 2008;Coomes and Grubb, 2000).…”
Section: Determinants Of Changesmentioning
confidence: 93%
See 1 more Smart Citation
“…As a result of the decrease in the exploitation of non-timber forest products such as litter raking, and also due to the ageing of tree stands, a thicker layer of beech litter accumulates, which results in top soil acidification and lower concentrations of nutrients (Barbier et al, 2008;Trap et al, 2013). A shift from mull to moder humus form has previously been observed along the beech stand chronosequence (Trap et al, 2011). The properties of the topsoil such as moisture and nutrient loading could also be deteriorated by the fine root network of the ageing beech trees, which by the uptake of resources reduces soil water supply and nutrient availability (Barbier et al, 2008;Coomes and Grubb, 2000).…”
Section: Determinants Of Changesmentioning
confidence: 93%
“…It has been shown that, along with the ageing of the beech stands, a thicker layer of beech litter has accumulated, which has resulted in top soil acidification and lower concentrations of nutrients as well as a shift from mull to moder humus observed along beech stand chronosequences (Barbier et al, 2008;Trap et al, 2011Trap et al, , 2013. Therefore, the change of soil conditions due to the ageing of the beech stands is more pronounced at less fertile sites than at more fertile ones because of the greater buffering capacity of the latter ones.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, soil nutrient accumulation was found to be controlled by litterfall, litter quality, and decomposition rate. Furthermore, accumulation of organic materials on the forest floor resulted from an imbalance between litter production and litter decomposition rates (Trap et al, 2011). 8).…”
Section: Relationships Between Litterfall Substrate Quality Decompomentioning
confidence: 99%
“…Our results agree with their findings as we found here that element concentration in soil organic matter did not depend on the presence of serpentine minerals, suggesting therefore that the uptake of essential elements was only influenced by plant requirements. The decomposition of beech litter seems to be little affected by soil nutrient availability (Trap et al, 2011), but serpentinitic soils are expected to display a lower mineralization rate because of the effect heavy metals have on microbial communities (Kazakou et al, 2008). Microbial and fungal communities may however be adapted in serpentinitic areas (e.g.…”
Section: Discussionmentioning
confidence: 99%